Assessment of noise effects of wind turbine on the general health of staff at wind farm of Manjil, Iran. Issue 1 (March 2016) - Abbasi, Milad; Monazzam, Mohammad Reza; Ebrahimi, Mohammad Hossein; Zakerian, Seyed Abolfazl; Dehghan, Somayeh Farhang; Akbarzadeh, Arash
The low-frequency noise generated by wind turbines is known as one of the risk factors for health. The aim of this study was to study the noise effect of wind turbine on the general health of staff at Manjil wind farm. For this purpose, workers were divided into three groups: maintenance, security, and office staff. Equivalent sound levels were measured for each group. Individual's health data were assessed using the 28-item General Health Questionnaire. Pearson correlation, analysis of variance, and multiple regression tests were used for data analysis in the R software. Statistical analysis results showed that the noise exposure is significantly correlated to all sub-scales of general health, except for depression. The low-frequency noise from wind turbines can cause harmful effects on the health of workers that are too close to the wind turbine and receive very intense noise.